PELATIHAN PENGEMBANGAN PERANGKAT PEMBELAJARAN BAGI GURU SEKOLAH DASAR NEGERI 100/VI PAMENANG II KABUPATEN MERANGIN PROPINSI JAMBI - Sofwan, Muhammad; Suci, Suci Hayati; Risdalina, Risdalina; Alirmansyah, Alirmansyah; Fauzan, Muhammad (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
Learning devices are key elements in ensuring that the teaching and learning process occurs effectively and systematically. With continuous curriculum changes, teachers are required to review and update their learning devices to maintain relevance to contemporary educational needs. This study aims to describe the training on learning device development for teachers at SD Negeri 100/VI Pamenang II, Merangin Regency, Jambi Province, which employs the Transfer of Knowledge (ToK) methodology. This training provides professional development for teacher competencies in developing learning devices that encompass teaching modules, instructional materials, learning media, student worksheets (LKPD), and assessment instruments. The interactive and participatory Transfer of Knowledge methodology enables teachers not only to update their knowledge but also to develop practical skills required for classroom instruction. The training outcomes demonstrate improvement in teacher competencies for developing learning devices that align with the independent curriculum in the planning dimension. This training is anticipated to yield long-term impacts in enhancing educational quality through more competent teachers and more effective learning devices that are relevant to student needs.